Milnacipran combined with pregabalin in fibromyalgia: a randomized, open-label study evaluating the safety and efficacy of adding milnacipran in patients with incomplete response to pregabalin - Mease, Philip J. (SAGE Publications, 2013)
OBJECTIVE: To evaluate the safety, tolerability, and efficacy of adding milnacipran to pregabalin in patients with fibromyalgia who have experienced an incomplete response to pregabalin. METHODS: In this randomized, multicenter, open-label study, patients received pregabalin 300 or 450 mg/day during a 4- to 12-week run-in period. Patients with weekly recall visual analog scale (VAS) pain score of at least 40 and up to 90, Patient Global Impression of Severity score of at least 4, and Patient Global Impression of Change (PGIC) score of at least 3 were classified as incomplete responders and randomized to continue pregabalin alone (n = 180) or receive milnacipran 100 mg/day added to pregabalin (n = 184). The primary efficacy parameter was responder status based on PGIC score of up to 2. The secondary efficacy parameter was change from randomization in weekly recall VAS pain score. Safety parameters included adverse events (AEs), vital signs, and clinical laboratory tests. RESULTS: The percentage of PGIC responders was significantly higher with milnacipran added to pregabalin (46.4%) than with pregabalin alone (20.8%; p < 0.001). Mean improvement from randomization in weekly recall VAS pain scores was greater in patients receiving milnacipran added to pregabalin (−20.77) than in patients receiving pregabalin alone (−6.43; p < 0.001). During the run-in period, the most common treatment-emergent AEs with pregabalin were dizziness (22.8%), somnolence (17.3%), and fatigue (9.1%). During the randomized period, the most common treatment-emergent AEs with milnacipran added to pregabalin were nausea (12.5%), fatigue (10.3%), and constipation (9.8%). CONCLUSIONS: In this exploratory, open-label study, adding milnacipran to pregabalin improved global status, pain, and other symptoms in patients with fibromyalgia with an incomplete response to pregabalin treatment.